FORMATION AND STAGES OF DEVELOPMENT OF THE SOCIAL ENVIRONMENT OF KARSHI CITY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This research article provides a comprehensive and systematic analysis of the historical changes that occurred in the social life of the city of Karshi between 1924 and 2024. The study covers issues of Soviet-era administrative-territorial reforms, industrialization processes, the activities of cultural and educational institutions, the demographic composition of the population, and the formation of social strata.